Empowerment of Women's Groups in Increasing Income through Nugget Businesses Made from Tilapia Fish in Macang Sakti Village Musi Banyuasin - Rahmat Kurniawan; Innike Abdillah Fahmi; Alhanannasir Alhanannasir; Rika Puspita Sari MZ; Irkhamiawan Ma'ruf; Ahmad Saribi (Universitas Muhammadiyah Palembang, 2024)
Tilapia is one of the freshwater fish that has been successfully cultivated by the people of Macang Sakti Village. Tilapia is rich in protein, fat, carbohydrates and other micronutrients that are good for growth and health. However, the high production rate of tilapia is not accompanied by the interest of the local community. This is because people prefer to consume wild freshwater fish obtained from rivers or swamps around. To increase consumer interest in tilapia, innovation is needed in the form of processing tilapia into fish nuggets by empowering women's groups as business actors. This effort also aims to increase family economic income. The location of Community Service was carried out in Macang Sakti Village, Sanga Desa District, Banyuasin Regency, South Sumatra, on October 22-26, 2023. The methods used were survey methods, counseling, discussions and demonstrations (practices) of processing tilapia into tilapia nuggets. The implementation of the activity was attended by more than 15 participants from among housewives with great enthusiasm. The results of this community service show that community service activities can increase participants' knowledge about the nutrition and benefits of tilapia and motivate them to actively consume and become entrepreneurs in tilapia processed products in the form of tilapia nuggets.